Timebased media / Rahman Amin - Amin, Rahman (National Design Center (NDC), 2021)
The present exhibition is different from past events as a result of two major events since then. This is the first time where students had to experience full On-Line Distance Learning (ODL). This was also the first time the 17 students Majoring Time Based Media succeeded in completing their studies. The teaching and learning of fine Arts is synonymous with the face to face (F2F) approach. Traditionally, this was the approach to build future graduates. However, the change in approach has brought about many questions. Among them include the effectiveness of on-line learning of the arts and the quality of the graduates. These questions are felt by the lecturers and students. The lecturers needed to ensure that their teaching and learning meets the level intended. Students also needed to ensure that what is conveyed can be digested and understood. These challenges are even more critical as this was the first time the Faculty of Fine Art will finally have graduates Majoring in the new Time Based Media. In order for the lecturers to achieve the objective of quality in graduates, lecturers need to also understand the problems that students face and find solutions through the screen. At the same time, students needed to adapt to the new normal. Most of them were staying with families that had also posed additional challenges that were very different from on-campus learning. Within the many limitations of the situation, learning finally proceeded to completion and thankfully all the students had succeeded in completing their assigned tasks to the level expected. Praises and congratulations are most appropriate to all students who have shown high commitment. Tireless efforts displayed through their grit are keys to their success. This same passion if practised and sustained, no matter the challenge, Insya Allah all will be overcome.